Multidisciplinary Management of Traumatic Brain Injury: Emergency Care, Early Physical Therapy, Laboratory Monitoring, and Radiologic Evaluation - Bajjah, Muhannad Adel Ali; Aqeel Mohammad Ali Hadi; Hasan Ahmed Yahya Abuhashim; Ali Yahia Ibrahim Shabaani; Hamdan Ali Hamdan Alghamdi; Solaiman Rashed Alfaheed; Naif Obaid Huda Alotaibi; Muhannad Adel Ali Bajjah; Ahmed Mohammed Hussain Abu Talib; Mohammed Ahmed AlObaid; Mohammed Salem Almotairi; Ali Ahmad Hadi Dagriri; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Traumatic brain injury (TBI) is a major global health concern affecting millions annually and causing substantial morbidity, mortality, and long term disability. It results from mechanical forces to the head, with severity ranging from mild concussion to severe intracranial injury. Closed head injuries—including contusions, diffuse axonal injury (DAI), and intracranial hematomas—represent the majority of cases. Aim: This study aims to highlight multidisciplinary approaches in the emergency care, early rehabilitation, laboratory assessment, and radiologic evaluation of TBI to improve outcomes and reduce secondary brain injury. Methods: A comprehensive review of TBI mechanisms, epidemiology, clinical presentation, diagnostic strategies, and acute management was conducted. Emphasis was placed on validated clinical tools such as the Glasgow Coma Scale (GCS), Canadian CT Head Rule, New Orleans Criteria, and PECARN guidelines for imaging decisions. Pathophysiological processes including primary and secondary injury cascades, intracranial pressure dynamics, and herniation syndromes were analyzed. Results: Effective TBI management requires early airway stabilization, prevention of hypoxia and hypotension, and timely imaging. Evidence based algorithms guide CT utilization and reduce unnecessary radiation exposure. Biomarkers such as GFAP and S100B show promise in predicting intracranial pathology in mild TBI. Severe TBI benefits from invasive ICP monitoring, targeted physiological goals, and multidisciplinary collaboration to reduce mortality. Rehabilitation involving physical, occupational, speech, and cognitive therapy significantly enhances functional outcomes. Conclusion: Integrated emergency management, prevention of secondary injury, structured imaging strategies, and coordinated rehabilitation improve TBI outcomes. A multidisciplinary team approach is essential to optimize survival, functional recovery, and long term quality of life.